Explicit versus Implicit Profit Sharing and the Determination of Wages: Microeconomic Evidence from the UK. - Bhargava, S; Jenkinson, T (1995)
This paper considers the claim that explicit profit sharing reduces the marginal cost of labor. This is contrasted with the view that implicit profit sharing occurs through wage bargaining. Using a macroeconomic data set from the UK we find no evidence that the introduction of profit sharing reduces base wages and, hence, the marginal cost of labor. However, firm profitability is found to have a positive effect on wages, which supports the hypothesis of implicit profit sharing through wage bargaining. These findings suggest that it is hard to justify the favorable tax treatment of profit-related pay found in the UK.